Características del consumo de ciprofloxacino iny 200 mg. en el servicio de medicina interna del hospital nacional almanzor aguinaga asenjo – essalud – chiclayo, enero – junio 2008 - Asmat Rubio, Martha Genara (2009)
This study had as objective to determinate the consume of Ciprofloxacino Iny. 200 mg. in service at Internal Medicine of National the Hospital Almanzor Aguinaga Asenjo – EsSalud – Chiclayo, Enero – Junio 2008. It was made a descriptive-retrospective study expressing the consume in DDD/100 beds/day The trend of consumption through a correlation analysis and the corresponding test of statistical significance, units consumed, diagnostic classification, bacterial resistance and cost on new soles. The consumption of ciprofloxacin inj. 200mg expressed in DDD/100 bed-days was 48.42%. Trend tends to variability over time, being not p 0.05 statistically significant. In the classification of diagnoses were more prevalent in the urinary tract infection, the percentage of bacterial resistance, 2.33% of all patients who received Ciprofloxacin inj. 200 mg. In the classification of diagnoses were more prevalent in the urinary tract infection, the percentage of bacterial resistance, 2.33% of all patients who received Ciprofloxacin inj. 200 mg.